Evaluation of a dysphagia screening system based on the Mann Assessment of Swallowing Ability for use in dependent older adults. Issue 4 (16th May 2016) - Ohira, Mariko; Ishida, Ryo; Maki, Yoshinobu; Ohkubo, Mai; Sugiyama, Tetsuya; Sakayori, Takaharu; Sato, Toru
Abstract : Aim: Dysphagia is common in dependent older adults. Thus, a method of evaluating eating and swallowing functions that can be used to diagnose and manage dysphagia in a simple and robust manner is required. In 2002, the Mann Assessment of Swallowing Ability (MASA) was introduced to identify dysphagia in acute‐stage stroke patients. As the MASA enables easy screening, it might also be applicable to dependent older adults if appropriate MASA cut‐off values and the most useful assessment items could be determined. In the present study, we attempted to determine suitable MASA cut‐off values, and the most useful assessment items for predicting aspiration and pharyngeal retention in dependent older adults. Methods: Using the MASA, we evaluated the eating and swallowing functions of 50 dependent older adults with dysphagia. All of the patients also underwent videoendoscopic‐based swallowing evaluations to detect aspiration and pharyngeal retention. The participants' characteristics and the utility of each assessment item were compared between various groups. Using the patients' videoendoscopic findings as a reference, receiver operating characteristic curve analysis was carried out to determine appropriate cut‐off values for predicting aspiration and pharyngeal retention in dependent older adults. Results: The optimal MASA cut‐off values for predicting aspiration and pharyngeal retention were 122 points and 151 points, respectively. A total of 17 of the 24 clinical items assessed by the MASA were found to be associated with aspiration in dependent older adults. Conclusions: The MASA is a useful screening tool for evaluating eating and swallowing functions in dependent older adults.Geriatr Gerontol Int 2017; 17: 561‐567 .